Creative bags : Shape, Material, Function. (Hong Kong, 2014)
Bags can take many forms - from grocery and shopping bags to totes and purses. While the retail variety is undergoing a conscientious upheaval as environmental considerations question the notion of "disposable", reuse is the growing trend. Along with brand considerations, this leads to new opportunities for revitalization, from portraying a company's products, or mission in a creative way to exploring new materials. Read more...